State-of-the-art and novel approaches to mild solubilization of inclusion bodies - Klausser, Robert; Kopp, Julian; Prada Brichtova, Eva; Gisperg, Florian; Elshazly, Mohamed; Spadiut, Oliver (Frontiers in Bioengineering and Biotechnology, 2023)
Throughout the twenty-first century, the view on inclusion bodies (IBs) has shifted from undesired by-products towards a targeted production strategy for recombinant proteins. Inclusion bodies can easily be separated from the crude extract after cell lysis and contain the product in high purity. However, additional solubilization and refolding steps are required in the processing of IBs to recover the native protein. These unit operations remain a highly empirical field of research in which processes are developed on a case-by-case basis using elaborate screening strategies. It has been shown that a reduction in denaturant concentration during protein solubilization can increase the subsequent refolding yield due to the preservation of correctly folded protein structure. Therefore, many novel solubilization techniques have been developed in the pursuit of mild solubilization conditions that avoid total protein denaturation. In this respect, ionic liquids have been investigated as promising agents, being able to solubilize amyloid-like aggregates and stabilize correctly folded protein structures at the same time.This review briefly summarizes the state-of-the-art of mild solubilization of IBs and highlights some challenges that prevent these novel techniques from being yet adopted in industry. We suggest mechanistic models based on the thermodynamics of protein unfolding with the aid of molecular dynamics simulations as a possible approach to solve these challenges in the future.